Kemampuan Komunikasi Matematis dalam Menyelesaikan Circle Problem Berdasarkan Self-Confidence Siswa SMP - Wasilatul Murtafiah; Reza Kusuma Setyansah; Dhea Alvita Nurcahyani (Universitas Hamzanwadi, 2021)
As part of 21st-century skills, communication is an essential skill for students. Students 'mathematical communication tends to below, one of which is influenced by students' self-confidence. For this reason, the purpose of this study is to describe the mathematical communication skills in solving circle problems based on students' self-confidence. Determining the subject using purposive sampling technique, namely from 36 students of class VIII SMP in Madiun, East Java, Indonesia, obtained two subjects with high self-confidence (SCT) and one subject with low self-confidence (SCR). A qualitative descriptive approach was used in this study. Tests and interviews were used as data collection techniques. Data were analyzed through reduction, presentation, and concluding. The results of this study include: SCT is capable while SCR is less able to meet the indicators of mathematical communication skills both in writing and orally at the stages of understanding problems, implementing plans, and checking back; and SCT can meet mathematical communication indicators both written and oral, while SCR is less able to meet written mathematical communication indicators but can verbally at the stage of planning completion. The level of self-confidence of students differentiates their mathematical communication skills in solving problems. Thus, a teacher needs to design an appropriate question to train students' mathematical communication skills with low self-confidence.